Peran Pekerja Sosial Dalam Memberikan Pelayanan Terhadap Anak Berhadapan dengan Hukum Di Rumah Aman "Sumur" Kabupaten Nganjuk - Sindy Lulut Fitriani; Silvia Fatmah Nurusshobah; Rini Hartini Rinda Andayani (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2025)
The Role of Social Workers in Providing Services is the main foundation in efforts to improve the welfare of individuals, families, groups, and communities. Social workers act as liaisons, advocates, and facilitators who help individuals access resources, overcome problems, and develop their potential. This study aims to understand and know in depth the role of social workers in providing services to children in conflict with the law at Rumah Aman “Sumur”, which includes 1) characteristics of informants, 2) the role of social workers in providing services to ABH, 3) supporting factors and inhibiting factors faced by social workers in providing services to ABH. This study uses a qualitative approach with a descriptive method. The data sources used are primary and secondary data sources, this study consists of six informants including social workers, ABH and professional companions. Data collection techniques in this study used the techniques of 1) in-depth interviews, 2) observation, 3) documentation studies. The results of the study indicate that the role of social workers given is quite optimal but 1) lack of support from families,2) lack of Human Resources (HR) and 3) lack of complete facilities and infrastructure in the services provided to ABH. Based on the results of the study, the researcher proposes a program, namely a means of building relationships between children and families at the "Sumur" Safe House in Nganjuk Regency using the social group work method with educational group and self-help group techniques.